2015
DOI: 10.1038/nrcardio.2015.124
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional HDL and atherosclerotic cardiovascular disease

Abstract: High-density lipoproteins (HDLs) protect against atherosclerosis by removing excess cholesterol from macrophages through the ATP-binding cassette transporter A1 (ABCA1) and ATP-binding cassette transporter G1 (ABCG1) pathways involved in reverse cholesterol transport. Factors that impair the availability of functional apolipoproteins or the activities of ABCA1 and ABCG1 could, therefore, strongly influence atherogenesis. HDL also inhibits lipid oxidation, restores endothelial function, exerts anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
519
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(542 citation statements)
references
References 134 publications
(226 reference statements)
10
519
1
12
Order By: Relevance
“…ApoA1 exposed to cyanate (HOCN), a product of HOSCN decomposition, lack the ability to control RCT and become pro-inflammatory. 80,81 Compared with native HDL, in ApoE-deficient mice, MPOmodified HDL lose anti-atherogenic properties as they unable to stabilize plaque, prevent foam cell formation, and suppress formation of macrophages with the pro-inflammatory phenotype. 34 MPO-modified HDL cannot bind to the HDL receptor and scavenger receptor B1, and promote proinflammatory activities such as upregulation of nuclear factor (NF)-κB and expression of adhesion molecules by ECs.…”
Section: Role Of Modified Apoa1 In Atherosclerosismentioning
confidence: 99%
“…ApoA1 exposed to cyanate (HOCN), a product of HOSCN decomposition, lack the ability to control RCT and become pro-inflammatory. 80,81 Compared with native HDL, in ApoE-deficient mice, MPOmodified HDL lose anti-atherogenic properties as they unable to stabilize plaque, prevent foam cell formation, and suppress formation of macrophages with the pro-inflammatory phenotype. 34 MPO-modified HDL cannot bind to the HDL receptor and scavenger receptor B1, and promote proinflammatory activities such as upregulation of nuclear factor (NF)-κB and expression of adhesion molecules by ECs.…”
Section: Role Of Modified Apoa1 In Atherosclerosismentioning
confidence: 99%
“…Other beneficial effects of apoA-I on CVD risk include its anti-inflammatory and antioxidative functions (reviewed in Rosenson et al [4]). In recent years, apoA-I has also been ascribed a glucose-controlling function, and studies show that apoA-I/HDL induces glucose uptake in cultured muscle myotubes (5-7) and stimulates insulin secretion from cultured b-cells (8).…”
mentioning
confidence: 99%
“…Interestingly, the intracellular miRNA levels were decreased in PBMCs after incubation with HDLs from healthy subjects, whereas they were increased after incubation with HDLs from CAD and ACS patients [7]. This differential cellular response to HDLs from healthy and diseased subjects may reflect physiological changes in HDL functions [150]. The analysis of intracellular pri-miRNA and pre-miRNA levels revealed that the observed changes in PBMCs might be due to transcriptional changes in miR-126-3p, but not miR-223-3p and miR92a-3p [7], raising the interesting hypothesis that PBMCs may export miRNAs to HDLs.…”
Section: Delivery Of Functional Hdl-carried Mirnas To Recipient Cellsmentioning
confidence: 96%